Overview on Steady-state Nuclear Methods for BWR Nuclear Core Design and Analysis - Ren-Tai Chiang (ASEAN Journal on Science and Technology for Development, 2018)
An overview on nuclear methods for boiling water reactors (BWR) core design and analysis is provided based on the ANS Standard 19.3. The steady-state BWR nuclear methods, composed of neutron cross section library generation method, lattice physics method and core physics method, are systematically reviewed and associated computer codes in common use for BWR core design and analysis are listed. Veri?cation and validation, the two complementary aspects in determining the range of applicability of the calculation system, are discussed extensively. The biases and uncertainties for the predictions from the calculation system over its demonstrated range of applicability are also discussed.